Market Timing, Maturity Mismatch, and Risk Management: Evidence from the Banking Industry - Benedikt Ruprecht; Oliver Entrop; Thomas Kick; Marco Wilkens (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
We investigate financial intermediaries interest rate risk management as the simultaneous decision of on-balance-sheet exposure and interest rate swap use. Our findings show that both decisions are substitute risk management strategies. Hausman exogeneity tests indicate that both decisions are only endogenous to one another for banks that start using swaps for the first time. For other banks, the maturity gap is exogenous to the decision to use swaps, but the reverse relationship is endogenous. For banks with trading activity, both decisions are exogenous to one another. We interpret these findings as the maturity gap being largely determined by customer liquidity needs, whereas the decision to use swaps relies on compliance with the interest rate risk regulation. Although hedging motives dominate, we find selective hedging behavior in swap use driven by the slope of the yield curve as well as by funding uncertainty.
Keywords: G21; G32; G33; 330